Expertise Moderates Incidentally Learned Associations Between Words and Images - Bruett, Heather; Fang, Xiaoping; Kamaraj, Deepan C.; Haley, Elizabeth; Coutanche, Marc N. (Frontiers in Psychology, 2018)
Individuals with expertise in a domain of knowledge demonstrate superior learning for information in their area of expertise, relative to non-experts. In this study, we investigated whether expertise benefits extend to learning associations between words and images that are encountered incidentally. Sport-knowledge-experts and non-sports-experts encountered previously unknown faces through a basic perceptual task. The faces were incidentally presented as candidates for a position in a sports team (a focus of knowledge for only the sports-experts) or for a job in a business (a focus of knowledge for both the sports-experts and non-sports-experts). Participants later received a series of surprise memory tests that tested: ability to recognize each face as being old (familiarity), the amount of information recalled about each face, and ability to select a correct face from equally familiar alternatives. Relative to non-sports-experts, participants with superior sports expertise were able to better recall the information associated with each face and could better select associated faces from similarly familiar options for the hypothetical prospective athletes. Hypothetical job candidates were recalled and selected at similar levels of performance in both groups. The groups were similarly familiar with the images (in a yes/no recognition memory test) when the faces were prospective athletes or job candidates. These findings suggest a specific effect of expertise on associative memory between words and images, but not for individual items, supporting a dissociation in how expertise modulates the human memory system for word-image pairings.